Language and Cultural Contact in Casablanca: Exploring South Korea’s Influence on Moroccan Society - Mellouk, Fatima (International Journal of Korean Humanities and Social Sciences, 2024)
Morocco has been home to many foreign cultures for decades. Language contact involves the mutual influence of languages between interacting individuals. East Asian people, among the many foreigners in Morocco, have contributed to various practices that attract young people. South Korean culture, in particular, is becoming increasingly popular due to the global reach of its entertainment sector. Consequently, a significant number of young Moroccans are influenced by Korean pop culture, which is evident in their behaviors. They watch Korean TV shows, listen to Korean music, dress in Korean fashion, and adopt Korean expressions and gestures. These influences contribute to a new, blended culture that isn’t entirely Moroccan or Korean. Despite limited academic research on this topic, understanding these cultural exchanges is crucial. This article will focus on Casablanca, with research conducted through questionnaires and interviews distributed online and in person, targeting individuals exposed to Korean culture.